Experimental challenges in ion channel research: uncovering basic principles of permeation and gating in potassium channels - Carvalho-de-Souza, Joao Luis; Saponaro, Andrea; Bassetto, C. A. Z.; Rauh, Oliver; Schroeder, Indra; Franciolini, Fabio; Catacuzzeno, Luigi; Bezanilla, Francisco; Thiel, Gerhard; Moroni, Anna (Advances in physics: X, 2022)
Biological ion channels precisely control the flow of ions across membranes in response to a range of physical and chemical stimuli. With their ability of transporting ions in a highly selective manner and of integrating regulatory cues, they are a source of inspiration for the construction of solid-state nanopores as sensors or switches for practical applications. Here, we summarize recent advancements in understanding the mechanisms of ion permeation and gating in channel proteins with a focus on the elementary steps of ion transport through the pore and on non-canonical modes of intramolecular communication between peripheral sensory domains and the central channel pore.